Biomarker insights into a methane-enriched Holocene peat-setting from "Doggerland" (central North Sea). (October 2022) - Blumenberg, Martin; Schlömer, Stefan; Reinhardt, Lutz; Scheeder, Georg; Pape, Thomas; Römer, Miriam
Peats formed widespread early after the Last Glacial Maximum around the coast of the Dogger Bank, the central high of the now flooded "Doggerland" (central North Sea). Here we present biomarker and gas geochemical insights into near-surface peat cored at 43 m water depth. Based on their probable age of ~10 ka before present (BP), the peats are likely part of the so-called basal Holocene peats. Pore waters in the samples document slight methane enrichments in peat layers (up to 250 nM methane vs 60 nM above the peat layer) and δ 13 C-values of methane ranging between ca. −46‰ and −60‰ PDB. Ethane, propane, and n -butane were also found and may either document upward migration of thermogenic hydrocarbons in the past or, more likely, peat-specific gases, which is indicated by accompanying abundant unsaturated analogs (i.e. ethene and propene). High concentrations of elemental sulfur (up to 19 wt.%) and sulfur-specific transformation products of plant triterpenoids (Des-A-triterpenoids) point to microbial generation during and/or slightly after peat-formation as hydrocarbon source. Biomarkers indicated that peats were formed in a variable environment with high contributions from higher plant wax material. However, a C20 highly branched isoprenoid (HBI) likely records abundant diatoms typical of an oligotrophic lake environment. In addition, all samples contained a suite of bacterial hopenes and fernenes (hop-17(21)-ene, diploptene, fern-7(8)-ene). A strongly fluctuating methane-flux and/or -turnover during peat formation is recorded in partially high 13 C-depletions of <−60‰ PDB of these biomarkers. This underlines the importance of peat layers for methane generation and consumption on "Doggerland" during the Holocene.